Beach law in the anthropocene - Timothy F. Smith; Justine Bell-James; John Page; Anja Scheffers; Giorgio Cataldo; Jennifer Corrin; Hossein Esmaeili; Miguel Frohlich; Adrienne Paul; Thomas Perroud; Jill Robbie; Hui Wang (Ocean & Coastal Management, 2026)

Stable isotopes (H, C, O) and 3D fluid flow modeling constraints on gold endowment along the Augmitto-Bouzan orogenic gold deposit (Abitibi subprovince, Quebec) - Guillaume Raymond; Georges Beaudoin; Benoît Quesnel; Christophe Scheffer; Crystal LaFlamme; René Therrien; John W. Molson (Mineralium Deposita, 2025)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Does variation in NIPA2 contribute to genetic generalized epilepsy? - Michael S. Hildebrand; John A. Damiano; Saul A. Mullen; Susannah T. Bellows; Ingrid E. Scheffer; Samuel F. Berkovic (Human Genetics, 2014)

Habitat-mediated cannibalism and microhabitat restriction in the stream invertebrate Gammarus pulex - Kathleen E. McGrath; Edwin T. H. M. Peeters; John A. J. Beijer; Marten Scheffer (Hydrobiologia, 2007)

Genetic mapping of sulfur assimilation genes reveals a QTL for onion bulb pungency - John McCallum; Meeghan Pither-Joyce; Martin Shaw; Fernand Kenel; Sheree Davis; Ruth Butler; John Scheffer; Jernej Jakse; Michael J. Havey (Theoretical and Applied Genetics, 2007)

Genetic mapping of a major gene affecting onion bulb fructan content - John McCallum; Andrew Clarke; Meeghan Pither-Joyce; Martin Shaw; Ruth Butler; Don Brash; John Scheffer; Ian Sims; Sjaak van Heusden; Masayoshi Shigyo; Michael J. Havey (Theoretical and Applied Genetics, 2006)

A simple model for evaluating the costs and benefits of aquatic macrophytes - Egbert H. Van Nes; Marcel. S. van den Berg; John S. Clayton; Hugo Coops; Marten Scheffer; Ekko van Ierland (Hydrobiologia, 1999)